The role of IL‐6 in the physiologic versus hypertensive blood pressure actions of angiotensin II. Issue 10 (20th October 2015) - Manhiani, M. Marlina; Seth, Dale M.; Banes‐Berceli, Amy K. L.; Satou, Ryosuke; Navar, L. Gabriel; Brands, Michael W.
Abstract: Angiotensin II (AngII) is a critical physiologic regulator of volume homeostasis and mean arterial pressure (MAP), yet it also is known to induce immune mechanisms that contribute to hypertension. This study determined the role of interleukin‐6 (IL‐6) in the physiologic effect of AngII to maintain normal MAP during low‐salt (LS) intake, and whether hypertension induced by plasma AngII concentrations measured during LS diet required IL‐6. IL‐6 knockout (KO) and wild‐type (WT) mice were placed on LS diet for 7 days, and MAP was measured 19 h/day with telemetry. MAP was not affected by LS in either group, averaging 101 ± 4 and 100 ± 4 mmHg in WT and KO mice, respectively, over the last 3 days. Seven days of ACEI decreased MAP ~25 mmHg in both groups. In other KO and WT mice, AngII was infused at 200 ng/kg per minute to approximate plasma AngII levels during LS. Surgical reduction of kidney mass and high‐salt diet were used to amplify the blood pressure effect. The increase in MAP after 7 days was not different, averaging 20 ± 5 and 22 ± 6 mmHg in WT and KO mice, respectively. Janus Kinase 2 (JAK2)/signal transducer of activated transcription (STAT3) phosphorylation were not affected by LS, but were increased by AngII infusion at 200 and 800 ng/kg per minute. These data suggest that physiologic levels of AngII do not activate or require IL‐6 to affect blood pressure significantly, whether AngII is maintaining blood pressure on LS diet or causing blood pressure to increase. JAK2/STAT3 activation, however, is tightly associated with AngII hypertension, even when caused by physiologic levels of AngII. Abstract : Physiologic levels of angiotensin II (AngII) do not activate or require interleukin‐6 to significantly affect blood pressure, whether AngII is maintaining blood pressure on low‐salt diet or causing blood pressure to increase. Janus Kinase 2/signal transducer of activated transcription activation, however, is tightly associated with AngII hypertension, even when caused by physiologic levels of AngII.